SOSIALISASI K-3 BAGI TEKNISI BENGKEL PENGELASAN SMAW DI KECAMATAN MEDAN TIMUR KOTA MEDAN - Ahmad Bakhori; Abdul Haris Nst; Muksin R Harahap; Muslih Nasution; Suhardi Napid; Bonar Harahap (Jurnal Pengabdian Mitra Masyarakat, 2022)
Electrode shielded arc welding or better known as Shielded Metal Arc Welding (SMAW) is welding using an electric arc as a metal melt heater. An electric arc is formed between the shielded electrode and the base metal. Because of the heat from the electric arc, the base metal and the tip of the electrode melt and freeze together (Wryosumarto, 2004). With the ability of reason, humans are able to use metal as a very vital life aid. Various kinds of machine construction, buildings and others can be created in the presence of metal. The metal raises the need for assembly or joining technology. One such connection technology is by welding (welding). The purpose of the Occupational Health and Safety Counseling for SMAW Welding Workshop Operators in Gang Buntu Village, Medan Timur District, Medan City are: So that the welding company makes procedures and rules for occupational health and safety in the workplace. Welding industry companies provide Personal Protective Equipment (ADP) for welding operators. Because the issue of occupational health and safety is very important to get attention because it is directly related to the productivity and efficiency of workers.